Depression and female gender associated with higher postoperative pain scores after sinonasal surgery - Schinz, Katharina; Steigerwald, Lukas; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Sievert, Matti; Rupp, Robin; Iro, Heinrich; Müller-Hübner, Sarina Katrin Ursel (Acta Oto-Laryngologica, 2021)
Background Although it is extremely necessary to reduce the number of opioids taken postoperatively after sinonasal surgery, this is the subject of controversial discussion. Objectives The objective of this study was to identify factors that predict higher postoperative pain scores (PPS) and the need for opioid analgesics after sinonasal surgery. Material and methods This was a retrospective study of n = 492 patients who underwent functional endoscopic sinus surgery (FESS), septoplasty or a combination of both in the Otolaryngology Department in Erlangen between January and December 2018. Postoperative pain using the numeric rating scale and the postoperative need for non-opioid and opioid analgesics in relation to demographic and surgical parameters were evaluated. Results Significant predictors for a higher pain score were depression (p = .009) and female gender (p < .001). A significant predictor of the need for postoperative opioids was the female gender (p < .001), whereas FESS alone showed a significantly lower need for opioids (p = .035) and a significantly lower PPS compared to septoplasty (p < .001). Conclusions and significance The study identified risk factors for a higher PPS and the need for opioids. The results indicated that reducing postoperative opioids might be possible in patients without these risk factors and might help guide individualized postoperative therapy.
CRIS-Team WoS Importer:2022-01-07